Pengaruh Model Pembelajaran CTL (Contextual Teaching and Learning) dan Media Belajar Bidang Miring terhadap Hasil Belajar Fisika Siswa Kelas X IPA di SMA Negeri 1 Siborongborong - Jan Piter Saragih; Ridwin Purba; Hisarma Saragih (Journal on Education, 2023)
The purpose of this study was to determine the effect of the CTL (contextual teaching learning) learning model and inclined plane learning media on the physics learning outcomes of class X IPA students at SMA Negeri 1 Siborongborong. This type of quasi-experimental research, research design with the provision of pretest and posttest. The research population was 252 students while the research sample was 72 students. The research sample was taken using purposive sampling technique. The research instrument uses a test. Data analysis with the -T test using SPPS 24. 00 for windows. Data from hypothesis testing for the influence of the CTL (contextual teaching learning) learning model and inclined plane learning media with a sig = 0. 000 <0. 05 and a tcount of 53. 70 > ttable 1. 688. So that the conclusion drawn is that there is an influence of the CTL learning model (contextual teaching learning) and inclined plane learning media on the physics learning outcomes of class X IPA students at SMA Negeri 1 Siborongborong